Clinical Profile and Pulmonary Function Tests among Females Exposed to Household Fuel Smoke in Bhavnagar, Gujarat: A Cross-Sectional Study - Patel Bhoomika D.; Dave Jigna D.; Mehta Jilan R; Engti Raktim; Gohel Kalpeshkumar K; Agrawal Siddhant V.; Pujari Shivkumar; Kalkotar Sandeep (Journal of Community Health Research, 2023)
Background: Studies from developing countries, suggest that exposure to smoke from household fuels like wood, animal dung, and kerosene used for domestic cooking, may be a risk factor for airway diseases among women. This study aims to find the effect of household fuel smoke among them through clinical profile and pulmonary function test. Methods: A cross-sectional study was conducted in respiratory medicine outpatient department of Sir T Hospital in Government Medical College, Bhavnagar. Female participants were interviewed with pretested semi-structured questionnaires. They included respiratory symptoms, housing condition, kitchen environment, type of household fuels, habits and history of passive smoking, the number of hours per day and the number of years spent for cooking (biomass exposure index). Chest x-ray and pulmonary function tests like spirometry and diffusion capacity of lungs were performed. Through purposive sampling, 100 female participants were included in the study, and data were analyzed using SPSS version 17.0 versions and Chi-square test. Results: The total number of participants was 100 with a mean age of 46.89±12. Three out of 10 had a history of passive smoking. Most of the patients suffered from dyspnea (84%) and cough (76%) as the main symptoms. Nearly half (43%) of them had a runny nose. 30% were passive smokers and 70% were nonsmokers. The patients’ cough and expectoration had a significant association with forced expiratory volume (FEV1)/ Forced Vital Capacity (FVC) > 70 (P=0.02). The study suggested that with aging, the odds for Fev1/FVC becoming